2016
DOI: 10.1021/acs.cgd.5b01268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Audible Sound on Protein Crystallization

Abstract: The successful crystallization of proteins is important because their molecular three-dimensional structures can be obtained through X-ray diffraction when in their crystalline form. Investigation of the crystallization process is beneficial for this purpose. We have reported that protein crystallization is sensitive to audible sound, which is commonly present but is often ignored. Here we investigate the effect of audible sound parameters, especially frequency, on a protein crystallization. We show a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 48 publications
(63 reference statements)
0
27
0
Order By: Relevance
“…duration between achievement of supersaturation and appearance of detectable crystals). Recently, pioneering work provided evidence of the possibilities of inducing sonocrystallization on macromolecules including proteins 1820 and conjugated polymers. 2123 It was reported that poly(3-hexylthiophene) (P3HT) polymers chains can assemble into nanofibers that are micrometers long under ultrasound in chloroform or toluene.…”
Section: Introductionmentioning
confidence: 99%
“…duration between achievement of supersaturation and appearance of detectable crystals). Recently, pioneering work provided evidence of the possibilities of inducing sonocrystallization on macromolecules including proteins 1820 and conjugated polymers. 2123 It was reported that poly(3-hexylthiophene) (P3HT) polymers chains can assemble into nanofibers that are micrometers long under ultrasound in chloroform or toluene.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, three kinds of DNA with different molecular weights were used for comparison which were calf DNA (~9900 kDa), salmon DNA (~660 kDa), and herring DNA (~66 kDa). Lysozyme was chosen as a model protein due to its accessibility and abundance and has been widely used in previous studies [36][37][38]. In a typical experiment, lysozyme was dissolved in protein buffer (0.05 M NaAc, pH 4.6) to obtain lysozyme solution while DNA solutions can be prepared by dissolving three kinds of DNA into lysozyme precipitant buffer (1.0 M NaCl, 0.05 M NaAc, pH 4.6).…”
Section: Resultsmentioning
confidence: 99%
“…Vibration is known to affect crystallization as a mechanical stimulus promoting nucleation. Although sound has been shown to improve the crystallization of proteins (Zhang et al, 2016), no scientific literature on sonic effects on the crystallization of inorganic compounds was found. Previous experiments on pure water droplets stimulated by acoustic 432 Hz using the Gas Discharge Visualization Camera (high voltage electrophotography) showed a significant increase in the size of the corona discharge (Rubik, unpublished data), which suggests a possible change in water structure (Korotkov and Orlov, 2010) from this stimulus.…”
Section: Discussionmentioning
confidence: 99%